Some issues of global problems in the changing system of values of the modern world - Natalia Hrushchynska (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Міжнародні відносини, економіка, країнознавство, туризм)
The article analyzes the peculiarities of global problems in the modern world system, their transformation, identification of more acute issues, taking into account the urgent issue of the security of each country, food security against the background of the growth of the total population of the planet. Issues of environmental protection and climate change. Modifications of global problems, taking into account wars and their consequences, along with the active phase of the Fourth Industrial Revolution, the development of artificial intelligence, which leads to the emergence of new professions, new forms of employment of the population, the development of humanity in general and, of course, affects the changes in the values of every society. The article analyzes the historical perspective of economic and social changes and the influence of technological processes, assesses the impact of the war on the economic and demographic components of society. It is noted that the results of the fourth industrial revolution, the emergence and development of artificial intelligence are a breakthrough for the survival of mankind. Artificial intelligence (AI) is rapidly transforming various industries, and environmental protection and climate change are no exception. The modern world transforms a person's way of life, forms of communication, changes the characteristics of relationships, views on the same things, manners of communication, and ultimately, values. In the articles of philosophers, economists, and psychologists who are engaged in researching the problems of forming the society of the future, the emergence of the technological structure of psychotechnologies and technologies related to moral responsibility is noted. Changes in the technological stages of society are accompanied by changes in society itself. Values influence people's desire to realize themselves and, accordingly, the sphere of employment. In the context of world transformations, there are changes in the values of society. Values can be divided into groups and everyone determines their priority (material, spiritual values (vital, moral, aesthetic), social, family values, the value of pleasure, health. Each person takes his place in society, which determines social values that depend from the environment, from needs, from goals, and they can change during life.Self-discovery is the deepest way of assessing one's values.